2011
DOI: 10.1038/tp.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Convergent functional genomics of anxiety disorders: translational identification of genes, biomarkers, pathways and mechanisms

Abstract: Anxiety disorders are prevalent and disabling yet understudied from a genetic standpoint, compared with other major psychiatric disorders such as bipolar disorder and schizophrenia. The fact that they are more common, diverse and perceived as embedded in normal life may explain this relative oversight. In addition, as for other psychiatric disorders, there are technical challenges related to the identification and validation of candidate genes and peripheral biomarkers. Human studies, particularly genetic ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 129 publications
4
71
0
1
Order By: Relevance
“…Of note, adult ADHD is linked with blunted Per2 expression (Baird et al, 2012). It is also interesting that the other clock genes with altered circadian profiles in ENT1 KO mice, Clock and Dbp, are associated with ADHD (Kissling et al, 2008;Roybal et al, 2007;Xu et al, 2010), bipolar disorder (Le-Niculescu et al, 2008;Lee et al, 2010;Shi et al, 2008;Soria et al, 2010), anxiety (Le-Niculescu et al, 2011a), and AUD (Le-Niculescu et al, 2011b;Le-Niculescu et al, 2008). Interestingly, ENT1 KO mice display mania-like behavior (Ruby et al, 2011) similar to Dbp KO mice (Le-Niculescu et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Of note, adult ADHD is linked with blunted Per2 expression (Baird et al, 2012). It is also interesting that the other clock genes with altered circadian profiles in ENT1 KO mice, Clock and Dbp, are associated with ADHD (Kissling et al, 2008;Roybal et al, 2007;Xu et al, 2010), bipolar disorder (Le-Niculescu et al, 2008;Lee et al, 2010;Shi et al, 2008;Soria et al, 2010), anxiety (Le-Niculescu et al, 2011a), and AUD (Le-Niculescu et al, 2011b;Le-Niculescu et al, 2008). Interestingly, ENT1 KO mice display mania-like behavior (Ruby et al, 2011) similar to Dbp KO mice (Le-Niculescu et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Two studies investigated differential gene expression in the amygdala during fear-conditioning based on previous experience of a homotypic (27) or heterotypic stressor (28). Gene expression was also investigated in blood and brain tissue of mice exposed to an anxiogenic vs. an anxiolytic drug using the convergent functional genomics approach (29). Another study examined withinbrain correlations of expression of mitochondrial and mitochondriarelated nuclear genes of rats exposed to inescapable stress (restraint stress with tail-shock) compared with unexposed CONs (30).…”
Section: Discussionmentioning
confidence: 99%
“…Although several showed an overlap with one or both of the other tissues, only nine factors (CREB1, FOXO3, JUN, MYC, MYCN, NFE2L2, NFKBIA, NR3C1, and TP53) were shared by all three, i.e., hippocampus, amygdala, and blood. Data generated by this study will undoubtedly complement other microarraybased studies that have also reported some of these genes (15)(16)(17).…”
mentioning
confidence: 52%